2021
DOI: 10.1002/cncr.33454
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of a novel FHL2 mutation by whole exome sequencing in twins with familial Waldenström macroglobulinemia

Abstract: BACKGROUND: Waldenström macroglobulinemia (WM) is a rare chronic B-cell lymphoma. Familial clustering of WM has been observed over the years. However, little is known about the contribution of inherited genetic variants to familial WM cases. METHODS: The authors performed whole exome sequencing (WES) of germline DNA samples from twins, one diagnosed with WM and the other diagnosed with immunoglobulin M monoclonal gammopathy of undetermined significance, and their healthy siblings. Bioinformatics analysis of pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…However, our study was conducted in the Chinese population in the time frame of 2003 to 2023, and the treatment regimen changed from traditional chemotherapy to regimens dominated by new agents such as rituximab, bortezomib, and BTKi. Our earlier work found that WM is characterized by familial co-morbidity, especially in first-degree relatives ( 18 ). We followed up on these patients and found that the proportion of hematologic SMs was not high, but the survival of this subgroup of patients was significantly lower than that of sporadic WM.…”
Section: Discussionmentioning
confidence: 97%
“…However, our study was conducted in the Chinese population in the time frame of 2003 to 2023, and the treatment regimen changed from traditional chemotherapy to regimens dominated by new agents such as rituximab, bortezomib, and BTKi. Our earlier work found that WM is characterized by familial co-morbidity, especially in first-degree relatives ( 18 ). We followed up on these patients and found that the proportion of hematologic SMs was not high, but the survival of this subgroup of patients was significantly lower than that of sporadic WM.…”
Section: Discussionmentioning
confidence: 97%